Tofacitinib in the Treatment of Moderate-to-Severe Rheumatoid Arthritis in China: A Cost-Effectiveness Analysis Based on a Mapping Algorithm Derived from a Chinese Population - Tan, Chongqing; Li, Sini; Yi, Lidan; Zeng, Xiaohui; Peng, Liubao; Qin, Shuxia; Wang, Liting; Wan, Xiaomin (Advances in therapy, 2021)
Introduction To estimate the cost-effectiveness of tofacitinib for patients with moderate-to-severe rheumatoid arthritis (RA) who failed conventional synthetic disease-modifying antirheumatic drugs from the Chinese healthcare system perspective. Methods An individual patient simulation model was used to estimate the lifetime cost and effectiveness. The comparator sequence commenced with etanercept, followed by rituximab-tocilizumab- non-biologic therapy. The intervention sequences were assumed to add tofacitinib to different positions in the comparator sequence. Quality-of-life estimates were generated by mapping Health Assessment Questionnaire scores to utility with the algorithm derived from a Chinese population. Scenario analyses, univariable and probabilistic sensitivity analyses were performed to evaluate the model uncertainty. Results Compared with the comparator sequence, patients receiving tofacitinib as the first-, second-, third- and fourth-line treatment gained additional 0.49, 0.59, 0.44 and 0.53 QALYs, respectively, and the use of tofacitinib as the first- and second-line treatment was less costly, whereas the use of tofacitinib as the third- and fourth-line treatment cost an additional $234,998 and $381,116, respectively. This produced an incremental cost-effectiveness ratio of $333.73 and $9669.34/QALY, respectively. Conclusion Tofacitinib is estimated to be dominant in both the first- and second-line settings and to be highly cost-effective in both the third- and fourth-line settings.